Relações entre variáveis funcionais e o desempenho dos empregados em uma instituição financeira - Borsari, Thiago Affonso (2018)
Human resources management processes have become more important in the corporate strategy of organizations. The present research focuses on the use of functional data in decision making in people management, based on the performance evaluation process in a financial institution. About the use of variables or indicators, the approach called HR Analytics is explored, which promotes the use of large amounts of data with the application of statistical techniques in search of a relationship between variables that can test hypotheses and present predictive models linked to Human Resources (HR) processes. As methodology, an exploratory analysis of data on the population of interest was carried out by means of data collection and functional variables of employees of a financial institution with the later application of statistical models. Complementary, a consultation was made to the managers on the relevance of the functional variables and their perception regarding the process of performance evaluation. The results of the two approaches were analyzed in order to find points of convergence for or against the importance of variables in employee performance. The exploratory analysis showed low significance of the functional variables when related to the performance of the employees. About the research questionnaire to managers, their perception is that the current processes of evaluation of performance and decision making in human resources management have shortcomings that could be overcome with the greater use of data. The comparison of the results of the two approaches presented some convergences that can be useful for the decision making in the evaluation of functional performance. As a conclusion, some variables can be considered as meaningful. However, the idea of enriching this study with the use of other variable, such as psychological profiles, seems promising.